2011
DOI: 10.1021/ol2007154
|View full text |Cite
|
Sign up to set email alerts
|

Electrophile-Driven Regioselective Synthesis of Functionalized Quinolines

Abstract: Highly substituted 3-iodoquinolines bearing different alkyl and aryl moieties can be synthesized in moderate to excellent yields (up to 99%) by 6-endo-dig iodocyclization of 2-tosylaminophenylprop-1-yn-3-ols with molecular iodine (I(2)) under mild conditions. The cyclization is highly regioselective and the resulting 3-iodoquinolines can be further functionalized by various coupling reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(28 citation statements)
references
References 84 publications
0
28
0
Order By: Relevance
“…81 Changing the protecting group of nitrogen from dimethyl to Ts, Liang et al reported an efficient and highly regioselective protocol for preparing 3-iodoquinolines (Scheme 75). 82 The resulting 3-iodoquinolines can be further functionalized by using cross-coupling reactions.…”
Section: 2 Cyclization Involving Alkynesmentioning
confidence: 99%
“…81 Changing the protecting group of nitrogen from dimethyl to Ts, Liang et al reported an efficient and highly regioselective protocol for preparing 3-iodoquinolines (Scheme 75). 82 The resulting 3-iodoquinolines can be further functionalized by using cross-coupling reactions.…”
Section: 2 Cyclization Involving Alkynesmentioning
confidence: 99%
“…Quinolines, quinolinium salts, and isoquinolinium salts are highly important alkaloids with numerous valuable biological activities and other applications, some of which are shown in Figure . For example, 1‐benzyl‐quinolinium chloride can be used to suppress the corrosion process .…”
Section: Introductionmentioning
confidence: 99%
“…Quinolines are potential therapeutics with antimalarial, anti‐asthmatic, anti‐hypertensive, antibacterial, anti‐inflammatory, and tyrosine kinase inhibitive activities . In particular, halogen‐containing quinolines are of special interest because the halogen atoms could not only play an important role in the bioactivity of the compounds, but are also very useful for further elaboration to other complex molecules . Since the late 1800s, there have been many advances in the synthesis of quinolines, as exemplified by various conventional methods such as Pfitzinger, Friedländer, Skraup, Doebner‐von Miller, Conrad‐Limpach‐Knorr and Combes, as well as a number of recently developed new methods .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 As an environmentally benign oxidizing agent, molecular iodine has been used in various organic reactions. [5][6][7][8][9] It is known that secondary alcohols are readily converted into ketones, while primary alcohols can be first oxidized into the aldehydes and further into the carboxylic acids or their derivatives. Thus, the oxidation of primary alcohols to the corresponding carbonyl compounds is not so easily controlled as that of secondary alcohols.…”
Section: Introductionmentioning
confidence: 99%